Clinical Outcomes After Nonoperative Management of Large Acute Traumatic Subdural Hematomas in Older Patients: A Propensity-Scored Retrospective Analysis. Issue 2 (1st November 2022) - Kashkoush, Ahmed I.; Whiting, Benjamin B.; Desai, Ansh; Petitt, Jordan C.; El-Abtah, Mohamed E.; Mcmillan, Aubrey; Finocchiaro, Roman; Hu, Song; Kelly, Michael L.
Abstract : BACKGROUND: Large (≥1 cm) acute traumatic subdural hematomas (aSDHs) are neurosurgical emergencies. Elderly patients with asymptomatic large aSDHs may benefit from conservative management. OBJECTIVE: To investigate inpatient mortality after conservative management of large aSDHs. METHODS: Single-center retrospective review of adult patients with traumatic brain injury from 2018 to 2021 revealed 45 large aSDHs that met inclusion criteria. Inpatient outcomes included mortality, length of stay, and discharge disposition. Follow-up data included rate of surgery for chronic SDH progression. Patients with large aSDHs were 2:1 propensity score–matched to patients with small (<1 cm) aSDHs based on age, Injury Severity Scale, Glasgow Coma Scale, and Rotterdam computed tomography scale. RESULTS: Median age (78 years), sex (male 52%), and race (Caucasian 91%) were similar between both groups. Inpatient outcomes including length of stay ( P = .32), mortality ( P = .37), and discharge home ( P = .28) were similar between those with small and large aSDHs. On multivariate logistic regression (odds ratio [95% CI]), increased in-hospital mortality was predicted by Injury Severity Scale (1.3 [1.0-1.6]), Rotterdam computed tomography scale 3 to 4 (99.5 [2.1-4754.0), parafalcine (28.3 [1.7-461.7]), tentorial location (196.7 [2.9-13 325.6]), or presence of an intracranial contusion (52.8 [4.0-690.1]). Patients with large aSDHs trended toward higher progression on follow-up computed tomography of the head (36% vs 16%; P = .225) and higher rates of chronic SDH surgery (25% vs 7%; P = .110). CONCLUSION: In conservatively managed patients with minimal symptoms and mass effect on computed tomography of the head, increasing SDH size did not contribute to worsened in-hospital mortality or length of stay. Patients with large aSDHs may undergo an initial course of nonoperative management if symptoms and the degree of mass effect are mild. Abstract :